Two hundreds years of neighbourhood expansion in Seremban municipality area, Malaysia - Shaharudin Idrus,; Abdul Samad Hadi,; Abdul Hadi Harman Shah,; Erza Haslinda Sharani,; Marlia Zahura Baharudin, (Environmental Management Society, Malaysia, 2009)
Malaysia has been experiencing rapid neighborhood expansion since the 1970s in the Seremban Municipal area. Due to the rapid urbanization process, more than two thirds of the people now live in urban areas, and the number is expected to increase further in the years towards 2020. A major land area in the urban area is set for housing development; that land was converted from agriculture and forest land. Foreign direct investment, the availability of human capital, the availability of suitable land; and the availability of current technology are the major driving forces for escalating housing construction to meet demand. Nevertheless, the construction of housing estates has resulted in positive and negative impacts especially on the physical environment and social well-being. This article discusses the neighborhood expansion in the Seremban municipal area for the past two hundreds years. The expansion of the housing schemes especially in the 1970s under the New Economic Policy (NEP) was to match the economic vibrancy and increase of the social well-being in the municipality. The key argument here is how livable are the current housing estates in the multi-ethnic society of Malaysia? The Malaysian society comprises the Malays, Chinese, Indians and others, who have their own values and preferences, and above all differing affordabilities that will be the major challenge in Malaysian housing expansion. The article presents some findings on the study of socio-spatial dimension, structures and patterns of housing expansion in Seremban Municipality area